A viabilidade econômica e técnica da utilização de poços tubulares para o abastecimento de água na região de Belém e Ananindeua - KOURY, Felipe de Souza Moitta (Universidade Federal do Pará, 2019)
In the next decades, the economic development and the stability politics of the nations they will be on to the water availability candy in its territories. The water will be a so important product how much the oil or the technology and its scarcity or abundant can will provoke the start of unexpected conflicts in scale. This problem has as initial step for its good solution, the complete knowledge of the hydrologic cycle, that will technical allow to an evaluation correct insurance and of the availability of the hidrics resources of a region. And an important part is to understand what it happens with the ground waters, that are without doubt the part most unknown of the related cycle. E also to know the availability of the water-bearing systems and the quality of its waters is primordial for the establishment of one politics of management of ground water. The full exploitation of the underground hydrics resources depends on hydrogeological comments, analyses and conclusions that more allow the captation of the water in the adjusted places in depth terms, outflow and quality of the water. In such a way, the stages of the developed work had been the following ones: characteristics of the hydroclimatic and meteorological picture, evaluation of the geologic units, register in cadastre of deep tubular wells, chemical analysis of waters of the water-bearing ones of the region, evaluation of the degree of vulnerability of ground waters, calculate of the hydrics reserves and economic comparison enters ground water and superficial water for choice of the source to be caught for the system of public supplying. The population of Belém esteem for the year of 2006 is of 1.444.618 habitants, distributed in an area of 210 km² and for Ananindeua 488.106 habitants, in a 184 area of km². The climate of the region is equatorial humid, of the Af type, and the hydric crocking indicates that in the period of January the September has water excess in the ground, what results in superficial draining and infiltration of this water in the ground, and that in the months of October and November has water deficiency in the ground. The waters of the free aquifer are acids, presenting pH between 3,4 and 5,7, low electric condutivit. Are labeled chloride sodium or bicarbonate sodium. The waters of the Pirabas aquifer are of excellent quality and are classified as bicarbonated calcic, alkaline and present high values of electric condutivit, hardness and alkalinity of bicarbonate. The Pirabas aquifer configures as the best option for ground water exploration, having wells between 250 and 350 meters of depth, they supply the outflows of 250 up to 380 m³/h, being for these characteristics the most indicated for public supplying. The degree of vulnerability of the Pirabas aquifer is considered low to neglecter, due to thickness of the zone not saturated and the lytologics and structural characteristics, being more protected of the infiltration of contaminantes and therefore less vulnerable to the pollution. The region of Belém and Ananindeua has reserve total of ground water of 10,71 billion cubical meters in the year, and a reserve of exploration of 134,7 million cubical meters in the year, represents all regulating reserve more 30% of the permanent reserve in the 50 years. The per capita underground hydric availability is of 190 liters/day. As the addition of the demand until the year of 2025 it is of 57,03 million cubical meters of water in the year, will be necessary to take care of to this addition the construction of 65 deep wells with outflow measured of 250 m³/h, operating in a regimen of bombardment of 16 hours in the day or then 52 wells if the regimen of bombardment will be of 20 hours in the day. Being also that the necessary investment for the construction of these wells will be made title throughout this period of 20 years. Since the price of the cubical meter of groundwater is 33.60% cheaper than the superficial water, then this option if configures as the most indicated to take care of the public supplying. Considering the raised hypotheses, it can be concluded that ground water use proceeding from the Pirabas aquifer is the best option for magnifying of the system of water supply for the region of Belém and Ananindeua. A time that the decision taken for the COSANPA was of magnifying of the system of water supply of Belém and Ananindeua from superficial waters the this option alone will be applicable after 2025, where for the estimates of population growth the system will need magnifying again.